Investigation of Benzimidazole Derivatives in Molecular Targets for Breast Cancer Treatment: A Comprehensive Review - Katiyar, Pratima; Kalpana; Srivastava, Aditi; Singh, Chandra Mohan (Critical reviews in oncogenesis, 2025)
This article provides a basic summary of computational research on benzimidazole and its molecular targets in breast cancer (BC) drug discovery. The drug development process is streamlined, expenses are decreased, and the possibility of finding successful therapies for this difficult illness is increased with the use of computational tools. The utilization of benzimidazole derivatives in medication research and discovery is discussed, along with the results of benzimidazole derivative-related clinical trials conducted against blood cancer during the previous five years. Additionally, it includes analysis of changes in structure and how they affect pharmacology. The structure-based method and other computational tools used in drug development are also covered, as well as the importance of structural information such as stereochemistry, physiological action, and the use of spectroscopic methods like NMR and X-ray crystallography in understanding the interactions between bioactive compounds and receptors. The article highlights the potential of benzimidazoles as bioactive heterocyclic molecules with various biological activities, including antimicrobial and anti-cancer properties.